Functionalized polysiloxanes with perylene diimides and poly(ethylene glycol): Synthesis and properties. (5th January 2022) - Glosz, Karolina; Ledwon, Przemyslaw; Motyka, Radoslaw; Stolarczyk, Agnieszka; Gusev, Ivan; Blacha-Grzechnik, Agata; Waskiewicz, Sylwia; Kaluzynski, Piotr; Lapkowski, Mieczyslaw
Graphical abstract: Highlights: A series of polymethylsiloxane were synthetized via catalytic hydrosilylation. Perylene diimides acted as the active functional component of the polymers. The use of poly(ethylene glycol)s co-grafts significant improved solubility. Abstract: Herein, we examine the synthesis of new polymers and characterize their physicochemical properties. A series of novel polymers based on polymethylsiloxane by catalytic hydrosilylation were successfully designed and synthetized. In order to enhance the polymers solubility, perylene diimide acted as the active functional group and poly(ethylene glycol) acted as the property modifying agent. Their structure was studied using 1 H NMR and infrared spectroscopy. Grafting of PDI-allyl on polysiloxane led to mostly insoluble polymer. In contrast, the addition of poly(ethylene glycol)s co-grafts promoted good solubility in common solvents. UV–Vis and fluorescence spectroscopy, and atomic force microscopy were used to characterize the polymers. The generation of singlet oxygen by the prepared polymers, in which perylene diimide was the photosensitizer, demonstrated their applicability.